Evaluación de cuatro raciones alimenticias en el crecimiento y engorde de cuyes mejorados (Cavia porcellus) en el centro académico Miraflores de la UNSM-T/FCA, región San Martín - Sanchez Ruiz, Karen Elizabeth (2015)
The present research aimed to evaluate the effect of four food rations based on grass King Grass; Balanced food; King Grass Grass King's Eritrina and more Diet Foods in growth and fattening improved guinea pigs (Peru Line) and determine the effect of the most suitable food ration on weight gain, feed conversion and profitability. The research was conducted in guinea pigs Module Academic Center Miraflores Agricultural Faculty of Agricultural Sciences UNSM-T, the district Shilcayo, province and region of San Martín. The Statistical Completely randomized design was used with four treatments and two replications. The information obtained was processed using SPSS 19 statistical software, which uses the P-value comparison significant at confidence levels of 0.05 and 0.01 differences in the analysis of variance (ANOVA) and test Duncan's multiple range P ≤ 0.05. The variables evaluated were: initial and final weight, gain weight, mortality, food consumption, feed conversion and profitability. The results indicate that treatments T1 (Diet Foods (Cuyina) and T3 (King Grass's Diet Foods) were the most decisive diet which influenced the growth and fattening, obtaining the variable final body weight (g), average 1270.0 and 1237.25 grams. The average FCR scored 2.44 and 4.84, rewarding financially with 41.6% and 18.65% of net profit.